Upaya Penggugatan Tanggung Jawab Hukum Atas Kejahatan Internasional Yang Melibatkan Pasukan Perdamaian Perserikatan Bangsa-Bangsa Berdasarkan Ketentuan Hukum Internasional (Studi Putusan Rechtbank Den Haag 16 Juli 2014 atas Gugatan Stichting Mothers of Srebrenica Bosnia terhadap Negara Belanda dan PBB) - Amanda Ulinnuha; Prasetyo Hadi Purwandoko; Diah Apriani Atika Sari (BELLI AC PACIS, 2018)
The objective of this research is to analyze the responsibility of the United Nations (UN) and its Member States as subjects of international law, in relation to law enforcement against international crime involving the act of omission and/or the act of commission by on-duty peacekeeping soldiers in UN authorized Peacekeeping Operation. This legal research is a normative legal research. It sets sources of international law containing regulations and theories concerning responsibility of international organizations and states and immunity of the UN and its agents, as well as judicial decision established by the Dutch District Court for the Srebrenica Genocide as its normative grounds. This legal research is an analytical research. This legal research applies statute approach, case approach and conceptual approach and uses primary and secondary legal materials. The result of this research shows that both the UN and Member States can be held responsible for the conduct of their troops in the midst of peacekeeping operation as long as it is attributed to them.